Pursuing a corporate understanding of service-learning in nursing education: A case study - Julie, H (South African Journal of Higher Education, 2016)
A corporate definition of service learning could help mainstreaming service-learning in higher education institutions. Concepts like ‘service-learning’, ‘community engagement’ and ‘community service’ tend to be used interchangeably. It is thus imperative to start from a common understanding of this related concepts. Therefore, this article discusses the development of a definition of SL for a school of nursing. The democratic process of the nominal group technique allowed the academics to discuss conflicting points openly during the consensus-seeking process. The thematic analysis, based on frequency scores, identified ‘equal tri-partnership’, ‘teaching and learning process’, ‘reflective practitioners’, ‘community needs’, ‘community development’, ‘shared values’ and ‘community engagement’ as the essential concepts to be included in the definition of service-learning. It can be concluded that the final SL concept list was formulated due to the academics’ willingness to examine their individual practice theories with the purpose of developing a shared understanding of these concepts.